ANALGESIC EFFECTS OF METHANOLIC SEED EXTRACT OF Vigna subterranea (Fabaceae) IN ALBINO MICE - MUIDEEN OLADEPO, OLAYIDE; AMEERA ADAMU, AISHA; ABUBAKAR MAHDI, MUHAMMAD; SALAWU, OLUWAKANYINSOLA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Vigna subterranea is claimed traditionally to possess antioxidant and analgesic effects. Thisstudy is aimed at evaluating the possible analgesic claims of Vigna subterranea. Anacutetoxicity study of the extract was carried out using the Lorke‘s method. The central and peripheral analgesic effects were assessed using a hot plate and acetic acid-induced writhingtestsrespectively. The methanolic seed extract of Vigna subterranea (MEVS) at doses of 250and500mg/kg produced significant central analgesic activity (P<0.05) when compared to the control. Similarly, the extract at doses 250 and 500 mg/kg significantly reduced the number of writhes. The percentage inhibition of writhing is in ascending order of 23.85, 35.98 and 43.09%inadose-dependent manner (125 mg/kg to 500 mg/kg). Findings from this research lend credencetothe folkloric use of Vigna subterranea and may serve as a basis for development of pureanalgesic compounds from it.